The impact of workload and emotional demands on turnover intentions: the mediating and moderating effects of job burnout - Hung, Wen-Yu; Chang, I-Hsiung; Hsiao, Yueh-Chih (Frontiers in Psychology, 2025)
IntroductionAlthough workload and emotional demands are recognized as key antecedents of job burnout, research focusing on preschool teachers has rarely compared their relative effects or explored whether burnout may function simultaneously as a mediator and a moderator. Using the Job Demands-Resources (JD-R) and Conservation of Resources (COR) frameworks, this study examines how these job demands influence preschool teachers' turnover intention through job burnout, and whether burnout amplifies these associations.MethodsA two-stage survey was administered to 200 preschool teachers in Taiwan. Measures included workload, emotional demands, job burnout, and turnover intention. Data were analyzed using mediation and moderation analysis.ResultsWorkload and emotional demands both significantly and positively predicted turnover intention through job burnout. Moreover, job burnout moderated the effect of workload on turnover intention, with the relationship becoming stronger at higher burnout levels.DiscussionThese findings underscore the dual role of job burnout and highlight the need for early childhood education administrators to reduce job demands, implement burnout prevention strategies, and stabilize the preschool teaching workforce.